Beneath the stairs : a novel - Fawcett, Jennifer (Atria Books, 2022)
"In this spine-tingling, atmospheric debut for fans of Jennifer McMahon, Simone St. James, and Chris Bohjalian, a woman returns to her hometown after her childhood friend attempts suicide at a local haunted house-the same place where a traumatic incident shattered their lives twenty years ago. Few in sleepy Sumner's Mills have stumbled across the Octagon House hidden deep in the woods. Even fewer are brave enough to trespass. A man had killed his wife and two young daughters there, a shocking, gruesome crime that the sleepy upstate New York town tried to bury. One summer night, an emboldened fourteen-year-old Clare and her best friend, Abby, ventured into the Octagon House. Clare came out, but a piece of Abby never did. Twenty years later, an adult Clare receives word that Abby has attempted suicide at the Octagon House and now lies in a coma. With little to lose and still grieving after a personal tragedy, Clare returns to her roots to uncover the darkness responsible for Abby's accident. An eerie page-turner, Beneath the Stairs is about the trauma that follows us from childhood to adulthood and returning to the beginning to reach the end"--